Analisis Model Matematika Pengaruh Feline Immunodeficiency Virus pada Sistem Imun Kucing - Fanesa Larasati; Dewi Murni (UNIVERSITAS NEGERI PADANG, 2023)
FIV is a virus that attacks the cat's immunity and causes AIDS-like in cats. FIV utilizes immune cells as receptors for initial attachment, then will form DNA that enters the cell nucleus and interacts with immune cell DNA. The results of this DNA replication form a new virus that will continue to multiply in the cell membrane. The purpose of this research is to form a mathematical model that examines how the dynamics of the FIV virus moves and its effect on the cat's immune system. By analyzing the model, two fixed points are obtained, namely the fixed point and the fixed point for FIV disease in immune cells, where at that point the characteristics of the virus can be known. The results of the fixed point stability test using the eigenvalue and Routh Hurwitz criteria that have been carried out show that the number of immune cells slowly decreases due to the level of FIV virus replication in immune cells that are already infected and have immune disorders.